Rapid and Economical Drug-Eluting IOL Preparation via Thermoresponsive Agarose Coating for Effective Posterior Capsular Opacification Prevention - Chen, Siqi; Qin, Chen; Fang, Qiuna; Duo, Lan; Wang, Mengting; Deng, Zhennv; Chen, Hao; Lin, Quankui (Frontiers in Bioengineering and Biotechnology, 2022)
Posterior capsular opacification (PCO), the highest incidence complication after cataract surgery, is mainly due to the attachment, proliferation and migration of the residual lens epithelial cells (LECs). Although the drug eluting IOLs have been proved to be an effective way to prevent PCO incidence, its preparations are time-consuming and require tedious preparation steps. Herein, the thermo-reversible agarose is adopted to prepare drug eluting IOL. Such functional coating can be obtained easily by simple immersion in the anti-proliferative drug contained hot agarose and taken out for cooling, which not only does not affect the optical property, but also can effectively decrease the PCO incidence after intraocular implantation. As a result, the proposed agarose coating provides a rapid and economical alternative of drug eluting IOL fabrication for PCO preventing.